(untitled) (American Journal of Islam and Society, 2004)
On 7-9 May 2004, the SSHRC-funded, York University-based MCRI project on Diaspora, Islam, and Gender project held an international conference on “The Making of the Islamic Diaspora.” Under the directorship of Haideh Moghissi, Saeed Rahnema, and Mark Goodman, the event was held in Toronto and was cosponsored by the Ford Foundation Educational Project for Palestinians, the Atkinson Faculty of Liberal and Professional Studies, the York Centre for Refugee Studies, and the York Centre for Feminist Research. The conference brought together an impressive collection of scholars from around the world to share knowledge and insight into the challenges that face diaspora communities of emigrants, refugees, and exiles who originate from Islamic cultures, with a specific focus on the gender dimension of displacement. In addition to the invited guests and speakers, the conference was attended by approximately 50 academics, graduate students, and the public at large. The conference’s guest of honor was the Honorable Zahira Kamal, Minister of Women’s Affairs for the Palestinian National Authority, who participated in the conference and presented a keynote address at a dinner reception in her honor. The conference’s panels discussed themes related to identity formation, gender in diaspora, fundamentalism and human rights, the diaspora experience, and the media and representation. Nergis Canefe, for example, spoke about issues of religious identity and national belonging and noted that diasporas offer a site of new membership that is different than migrants and represent the flourishing of hybrid identities. She described the “common immigrant story,” where such socioeconomic barriers as racism, stereotyping, media representation, and difficulty in recertification make it extremely difficult to have a smooth life transition in a new country ...